Swath sonar multibeam EM122 bathymetry during METEOR cruise M84/2 with links to raw data files of bathymetry from Kerch. - Wintersteller, Paul; dos Santos Ferreira, Christian; Oelfke, Stefanie (PANGAEA, 2016)
Bathymetry based on data recorded during M84-2 between 26.02.2011 and 02.04.2011 in the Black Sea. The aim of the cruise was to investigate the gas hydrate distribution in sediments of the Black Sea by using several coring technics. In addition to the coring activities the installed EM122 and the PARASOUND system were used to detect gas emissions in the water column and to map large areas of possible seep sites.
Gridded bathymetry from multibeam echosounder EM122 data of the cruise M84/2, off Kerch and the eastern Crimea (2011)
Keywords: Bathymetry; Black Sea; Center for Marine Environmental Sciences; CT; DTM; File content; File format; File name; File size; M84/2; M84/2-track; MARUM; MBES; Meteor (1986); Underway cruise track measurements; Uniform resource locator/link to file